Kanpur Confectioneries Private Limited (A) - Dixit, Mukund R., (SAGE Knowledge. Cases., 2001)
This case describes a situation in which Alok Kumar Gupta, Chairman and Managing Director of Kanpur Confectioneries Private Limited (KCPL), a second-generation family business, has to decide whether to sign a contracting agreement with a larger player in the industry. It provides an opportunity to the participants of a management education program to get into Gupta's shoes, analyze the situation, evaluate the options, make a decision and think through an action plan. There are choices to be made between short-term profits and long-term development of the family brand, being engaged in all the functions of the business and focusing on one function, and dealing with one partner and multiple partners. The deal has its advantages in terms of saving advertising expenses, receiving a steady flow of income and gaining access to new competencies. However, there are risks as well, the most critical of which are loss of independence and dilution of the family brand "MKG".